Analisis Kebijakan Local Currency Settlement Antara Indonesia Dan China - Diva Nitasya Filza; Laura Sabila; Savira Felisia (Public Knowledge, 2024)
The purpose of this research is to discuss the Local Currency Settlement policy between Indonesia and China. Using the SWOT analysis method by collecting and evaluating data from various sources of academic publications. The relationship between Indonesia and China, both of which hold significant positions in the global order. The Local Currency Settlement (LCS) itself is a bilateral transaction settlement conducted between Indonesia and China to be able to use local currencies that are valid in each country. The implementation of LCS brings many benefits to Indonesia, including increased trade volume between Indonesia and China, ease of payment using local currencies, and strengthening bilateral relations between Indonesia in trade and investment.